PENGARUH PEMANFAATAN MEDIA GAMBAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - Andry Agustinus; Holilulloh Holilulloh; Hermi Yanzi (FKIP Unila, 2013)
The purpose of this study was to clarify the effect of the use of Media Images on learning outcomes of students of class VIII G on subjects Citizenship Education in SMP Negeri 1 Natarian South Lampung Academic Year 2012/2013. Principal techniques of data collection using questionnaire and supporting techniques is to use the documentation. The independent variable in this study is the media image, while the dependent variable is the student learning outcomes. Based on the results of hypothesis testing showed a significant relationship between the use of media images on the Grade VIII student learning outcomes G in SMP Negeri 1 Natarian South Lampung Academic Year 2012/2013. This is evidenced by the results of calculations using Chi square formula that count is greater than x2 x2 table, (x2 ≥ x2 hit tab), which is 16.73 ≥ 9.49 at significant level of 5% (0.05) and a significant level of 1% (0.01) obtained x2 x2 count is greater than the table, (x2 ≥ x2 hit tab), ie ≥ 13.3 16.73 with degrees of freedom = 4 ie with a contingency coefficient of 0.55 and contingent Cmax = 0.816 lies in the closeness effect above 0.56 (high category). So that the results of such testing is known that there are significant utilization of media images of the class VIII student learning outcomes in subjects G Citizenship Education in SMP Negeri 1 Natarian South Lampung Academic Year 2012/2013.Tujuan penelitian ini adalah untuk menjelaskan pengaruh pemanfaatan media Gambar terhadap hasil belajar siswa kelas VIII G pada mata pelajaran Pendidikan Kewarganegaraan di SMP Negeri 1 Natar Lampung Selatan Tahun Pelajaran 2012/2013. Berdasarkan hasil pengujian hipotesis menunjukan adanya pengaruh yang signifikan antara pemanfaatan media gambar terhadap hasil belajar siswa kelas VIII G di SMP Negeri 1 Natar Lampung Selatan Tahun Pelajaran 2012/2013. Ini dibuktikan dengan hasil perhitungan yang menggunakan rumus Chi kuadrat bahwa x2 hitung lebih besar dari x2 tabel, (x2 hit ≥ x2 tab), yaitu 16,73 ≥ 9,49 pada taraf signifikan 5% (0,05) dan taraf signifikan 1% (0,01) diperoleh x2 hitung lebih besar dari x2 tabel, (x2 hit ≥ x2 tab), yaitu 16,73 ≥ 13,3 dengan derajat kebebasan = 4 yakni dengan kontigensi 0,55 dan koefisien kontigen Cmaks = 0,816 terletak pada keeratan pengaruh diatas 0,56 (kategori tinggi). Sehingga dari hasil pengujian tersebut diketahui bahwa terdapat pengaruh pemanfaatan media gambar terhadap hasil belajar siswa kelas VIII G pada mata pelajaran Pendidikan Kewarganegaraan di SMP Negeri 1 Natar Lampung Selatan Tahun Pelajaran 2012/2013.Kata kunci : hasil belajar, pemanfaatan media gambar, pembelajaran kewarganegaraan